Caribbean sovereignty, development, and democracy in an age of globalization - Lewis, Linden (Routledge advances in international relations and global politics, 2013)
Many of the nations of the Caribbean that have become independent states have maintained as a central, organizing, nationalist principle the importance in the beliefs of the ideals of sovereignty, democracy, and development. Yet in recent years, political instability, the relative size of these nations, and the increasing economic vulnerabilities of the region have generated much popular and policy discussions over the attainability of these goals. The geo-political significance of the region, its growing importance as a major transshipment gateway for illegal drugs coming from Latin Ameri.